Transformasi Model Bisnis pada Industri Kreatif: Studi Kasus Singayu Handmade Jewelry melalui Pendekatan Business Model Canvas - Fahrurrozi, Moh; Iswahyudi, M; Pradana, Dian Arief (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
The development of new business models is one of the strategies that can be pursued by creative industries to increase competitiveness and achieve sustainable growth. Singayu Handmade Jewelry is currently facing a number of significant challenges that hinder its growth. One of the main problems faced is the stagnation of sales growth, which is caused by a business model that has not been able to adapt to the changing market dynamics. This study aims to analyze the business model transformation strategy in the creative industry, especially in the Singayu Handmade Jewelry business, through the Business Model Canvas approach. The method used is a qualitative case study with data collection through interviews, observation, and document review. The results showed that Singayu transformed its business model by optimizing the nine component blocks of the business model canvas, such as strengthening and expanding distribution and marketing channels through e-commerce, social media and exhibitions, improving customer relationships through a more personalized approach, adding customization and collaboration services to increase revenue streams, strengthening human resource capabilities, adding key activities to increase brand awareness and sales, increasing cooperation with strategic partners and making efficiency in the cost structure.